Early-onset smoking theory of compulsivity development: a neurocognitive model for the development of compulsive tobacco smoking - Conti, Aldo Alberto; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2023)
According to the literature, individuals who start tobacco smoking during adolescence are at greater risk of developing severe tobacco addiction and a heavier smoking behaviour in comparison to individuals who uptake tobacco smoking during subsequent developmental stages. As suggested by animal models, this may be related to the unique neuroadaptive and neurotoxic effects of nicotine on adolescents’ fronto-striatal brain regions modulating cognitive control and impulsivity. Previous research has proposed that these neuroadaptive and neurotoxic effects may cause a heightened reward-oriented impulsive behaviour that may foster smoking relapses during quit attempts. However, developments in the field of Addiction Neuroscience have proposed drug addiction to represent a type of compulsive behaviour characterised by the persistent use of a particular drug despite evident adverse consequences. One brain region that has received increased attention in recent the years and that has been proposed to play a central role in modulating such compulsive drug seeking and using behaviour is the insular cortex. Lesion studies have shown that structural damages in the insular cortex may disrupt the smoking behaviour, while neuroimaging studies reported lower Gray Matter volume in the anterior insular cortex of chronic smokers compared to non-smokers, in addition to correlations between Gray Matter volume in the anterior insular cortex and measures of compulsive cigarette smoking. Based on the finding of our recent study reporting early onset smokers (mean age at regular smoking initiation= 13.2 years) to display lower Gray Matter and White Matter volume in the anterior insular cortex compared to late onset smokers (mean age at regular smoking initiation=18.0 years), we propose that the anterior insular cortex may play a central role in mediating the association between smoking uptake during adolescence and smoking heaviness/tobacco addiction during adulthood.